Citrus psorosis virus 24K protein interacts with citrus miRNA precursors, affects their processing and subsequent miRNA accumulation and target expression - Reyes, Carina Andrea (2016)
Sweet orange (Citrus sinensis), one of the most important fruit crops worldwide, may suffer from disease symptoms induced by virus infections, thus resulting in dramatic economic losses. Here, we show that the infection of sweet orange plants with two isolates of Citrus psorosis virus (CPsV) expressing different symptomatology alters the accumulation of a set of endogenous microRNAs (miRNAs). Within these miRNAs, miR156, miR167 and miR171 were the most down-regulated, with almost a three-fold reduction in infected samples. This down-regulation led to a concomitant up-regulation of some of their targets, such as Squamosa promoter-binding protein-like 9 and 13, as well as Scarecrow-like 6. The processing of miRNA precursors, pre-miR156 and premiR171, in sweet orange seems to be affected by the virus. For instance, virus infection increases the level of unprocessed precursors, which is accompanied by a concomitant decrease in mature species accumulation. miR156a primary transcript accumulation remained unaltered, thus strongly suggesting a processing deregulation for this transcript. The co-immunoprecipitation of viral 24K protein with pre-miR156a or pre-miR171a suggests that the alteration in the processing of these precursors might be caused by a direct or indirect interaction with this particular viral protein. This result is also consistent with the nuclear localization of both miRNA precursors and the CPsV 24K protein. This study contributes to the understanding of the manner in which a virus can alter host regulatory mechanisms, particularly miRNA biogenesis and target expression.